Parenting Patterns and Digital Media: A Case Study of the Socialization Process and Character Formation of Children in Kindergarten - Nurfadia Reski Azizan; Hajerah Hajerah; Fatimah Azzahrah; Naila Farila; Nur Sahrah Sarkia (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2026)
In the era of rapid digital transformation, digital media has permeated Indonesian family life, often functioning as a